(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
In today’s environment of rapid social, economic, and technological change, the importance of leadership qualities in managers is increasing. A successful organization requires not only formal management, but also the ability to inspire, guide, and unite the team around common goals. The article examines the key qualities of a leader-manager, their role in improving the effectiveness of an organization, as well as the characteristics of the formation of leadership competencies.